Chinese Politics : State, Society and the Market. - Gries, Peter (Asia's transformations., 2010)
Explores the changes occurring in China - what are the goals of political contestation, how are Chinese Communist Party leaders legitimizing their rule, who are the specific actors involved in contesting state legitimacy and what are the implications of changing state-society relations for the future viability of the People's Republic.